Concrete Technology in a Rapidly Growing Urban Environment €“ The Case of Dar es Salaam City - Makunza, John K. (Tanzania Journal of Engineering and Technology, 2023)
Concrete is a building material that is used in great quantities second only to our use of water. The ingredient materials of concrete include cement, fine and coarse aggregates plus a reasonable amount of water, and sometimes additives. The construction of various structures like, residential buildings, commercial buildings, hospitals, schools, bridges, etc, needs good quality concrete. Good modern technologies are needed by the construction industry in order to effectively construct buildings which are durable. A study has been done with the main objective of assessing the concrete technologies existing in rapid growing cities in Sub-Sahara Africa like Dar es Salaam, and the challenges faced in attaining good quality constructions. The study was done through site visits, observations, sampling and testing. From the results, it has been found that traditional concrete technologies are still prevailing, while new technologies are starting to be adopted. Also there is a problem of conformance to the standards. It was therefore recommended that investment in Cement production industries is needed and that regulatory bodies must enforce builders to adhere to the standards in order to yield good quality constructions. Keywords: Cement, Concrete, Concrete technology, Quality, Standard, Specifications